RETURN TO PARADISE - JAMES A MICHENER (NEW YORK THE DIAL PRESS, 2015)
Return to Paradise (1951) is a collection of short stories written by American author James A. Michener. The collection is a sequel to the Pulitzer Prize-winning book Tales of the South Pacific. In Return to Paradise, Michener revisits the islands and cultures of the South Pacific in the late 1940s, combining factual descriptions and tales set in such exotic places as Tahiti, Fiji, New Zealand, and Australia
SEQUEL TO TALES OF THE SOUTH PACIFIC.
Keywords: ENGLISH SHORT STORIES; ADVENTURE STORIES; HISTORICAL FICTION